Pengolahan permen susu untuk meningkatkan nilai ekonomi susu sapi - Fitriyani, Endah Nur (Nur Science Institute, 2025)
This community service activity aims to attract the interest of PKK members in Mujo hamlet by providing training in processing cow's milk so that it has a higher economic value. Cow milk processing is carried out to increase the selling price of milk because, in general, farmers only deposit it with collectors at a relatively low price. In contrast, when the milk is processed into a product, the selling price of the milk will increase. This increase in selling price will also provide more significant benefits to help increase family income. This community service is carried out in three stages: preparation, implementation, and evaluation. Training activities are carried out by practicing processing cow's milk into milk candy products. Milk candy was chosen because the raw materials and manufacturing process are easy to make, so PKK members can make it at home. Processed milk candy also has a fairly long shelf life, so it can minimize the risk of loss. The implementation of this service received a positive response from both participants and event organizers. In addition, similar activities can be carried out again because they have a positive impact, namely increasing knowledge and skills and fostering an entrepreneurial spirit for PKK members.